1988
DOI: 10.2478/cttr-2013-0587
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of the Wax Esters from the Cuticular Waxes of Green Tobacco Leaf

Abstract: Recent studies in our laboratory on the cuticular chemicals of green tobacco leaf have revealed the presence of wax esters, composed of fatty acids bound to fatty alcohols. Cuticular components of young green NC 2326 tobacco leaves were removed with methylene chloride, and partitioned between hexane and 80 % MeOH-H2O. The hexane-soluble fraction, which contained wax esters, paraffinic hydrocarbons, and fatty alcohols, was separated by silicic acid column chromatography, and the resulting wax ester fraction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Tsydendambaev et al [33] identified eight iso-BCFA (iso-15:0, -16:0, -17:0, -18:0, -20:0, -22:0, -24:0, and -26:0) on the green above-ground parts of four alpine plants, and Radunz [34] identified considerable quantities of iso-12:0, -14:0, -16:0, -18:0, and -22:0 BCFA in petals and chlorophyll-deficient leaves (averaging 9.0 and 4.2 % of total FA, respectively) of Antirrhinum majus and Nicotiana tabacum plants. In addition, BCFA have been identified in epi-cuticular waxes of several plants [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Tsydendambaev et al [33] identified eight iso-BCFA (iso-15:0, -16:0, -17:0, -18:0, -20:0, -22:0, -24:0, and -26:0) on the green above-ground parts of four alpine plants, and Radunz [34] identified considerable quantities of iso-12:0, -14:0, -16:0, -18:0, and -22:0 BCFA in petals and chlorophyll-deficient leaves (averaging 9.0 and 4.2 % of total FA, respectively) of Antirrhinum majus and Nicotiana tabacum plants. In addition, BCFA have been identified in epi-cuticular waxes of several plants [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The moderately abundant peaks (10-18%) one mass unit lower ( m/z 270 in WE 14:0-17:0) were radical cations [RCOOH] +• rationalized by a single hydrogen rearrangement ( 16,18 ). The C-C bond ␣ -cleavage at the carbonyl group provided small (4-10%) fragments [R'OCO] + ( m/z 241 in WE 14:0-17:0), which were practical for the confi rmation of the alcohol chain length ( 16,19 + ( m/z 61) ( 27 ). Their intensities ranged from 4-10% and 7-22%, respectively.…”
Section: Data Processingmentioning
confidence: 99%
“…However, radicals were eliminated from [R'−H] +• and [R'-C 2 H 5 ] +• ions yielding fragments indicative of the branching position. For instance, they appeared hydrogen transfer (16)(17)(18)(19). The moderately abundant peaks (10-18%) one mass unit lower ( m/z 270 in WE 14:0-17:0) were radical cations [RCOOH] +• rationalized by a single hydrogen rearrangement ( 16,18 ).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wax esters were present in trace amounts of up to 0.2 µg·cm -2 and ranged from C 35 to C 52 compounds, with the predominant wax ester being the C 35 compound. The composition of the nonpolar or hydrocarbonwax ester fraction resembled paraffinic hydrocarbons and wax esters observed for other plants, such as tobacco (Arrendale et al, 1988). The hydrocarbon-wax ester data for the resistant 'Sumner' were very similar to those for < Elliott' and, thus, are not presented.…”
Section: Resultsmentioning
confidence: 79%